1987
DOI: 10.2172/5694780
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature compatibility study of iridium (DOP-26 alloy) with graphite and plutonia

Abstract: This report outlines the materials compatibility tests conducted on DOP-26 iridium alloy and carbon. The carbon used was in the form of woven graphite as present in the impact shell used to encase plntonia in nuclear heat sources. In addition, compatibility tests of the DOP-26 alloy with plutonia are described. The reactivity observed in both systems is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For example, it has been shown that with partial pressures of oxygen on the order of at least 1.3*10 −3 Pa has a substantial influence on the grain growth of the system due to the oxidation of thorium at the surface of the iridium alloy cladding. 1,2 High quality argon gas sources have a nominal oxygen impurity <10 ppb (<10 −6 wt%). 25 This indicates that if the Ar gas at a pressure ≥260 kPa has 5 ppb oxygen impurities, it would be the equivalent to the partial pressure of oxygen used in previous experimentation.…”
Section: Potential Oxygen Sources At the Cfimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that with partial pressures of oxygen on the order of at least 1.3*10 −3 Pa has a substantial influence on the grain growth of the system due to the oxidation of thorium at the surface of the iridium alloy cladding. 1,2 High quality argon gas sources have a nominal oxygen impurity <10 ppb (<10 −6 wt%). 25 This indicates that if the Ar gas at a pressure ≥260 kPa has 5 ppb oxygen impurities, it would be the equivalent to the partial pressure of oxygen used in previous experimentation.…”
Section: Potential Oxygen Sources At the Cfimentioning
confidence: 99%
“…1 Iridium was chosen because of its high temperature strength, corrosion resistance, and compatibility with plutonia and graphite. [1][2][3] Tungsten is added for increased fabricability at high temperatures. 1 Thorium is added to improve the impact ductility of the alloy to prevent cracking during an impact event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that this diameter was 6,000 µm. ρ(hafnia) = 8.7659 g/cm 3 , 90.56% theoretical density ρ(urania) = 9.2064 g/cm 3 , 84% theoretical density ρ(plutonia) = 9.9596 g/cm 3 , 87.21% theoretical density Appendix II …”
Section: Appendix Imentioning
confidence: 99%
“…This alloy was developed by Oak Ridge National Laboratory, (1) with the alloy development complemented by axial testing and hightemperature compatibility studies conducted at Los Alamos National Laboratory. (2)(3) Two capsules are held in a Fineweave-Pierced Fabric † (FWPF) graphite impact shell (GIS), and two GISs are contained within an FWPF aeroshell module.…”
Section: Introductionmentioning
confidence: 99%